2021
DOI: 10.1186/s12935-021-01849-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic biomarker TUBA1C is correlated to immune cell infiltration in the tumor microenvironment of lung adenocarcinoma

Abstract: Background TUBA1C is a microtubule component that is involved in a variety of cancers. Our main objective was to investigate TUBA1C expression, its prognostic value, its potential biological functions, and its impact on the immune system of patients with lung adenocarcinoma (LUAD). Methods The Cancer Genome Atlas (TCGA), Gene Expression Profiling Interactive Analysis (GEPIA) and Immunohistochemistry Analysis were used to analyze TUBA1C expression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…Moreover, TUBA1C had different correlations with different immune cell subtypes, such as macrophages M0, M1, M2 (Figures 4J-L). Similarly, a previous study has illustrated that TUBA1C relates to the tumorinfiltrating cells of lung adenocarcinoma (Bian et al, 2021). We also demonstrated that TUBA1C was co-expressed with multiple immune-related genes, such as particular MHC genes, immune activation genes, immunosuppresive genes, chemokine receptor related genes, and chemokine related genes (Figures 5A-E).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Moreover, TUBA1C had different correlations with different immune cell subtypes, such as macrophages M0, M1, M2 (Figures 4J-L). Similarly, a previous study has illustrated that TUBA1C relates to the tumorinfiltrating cells of lung adenocarcinoma (Bian et al, 2021). We also demonstrated that TUBA1C was co-expressed with multiple immune-related genes, such as particular MHC genes, immune activation genes, immunosuppresive genes, chemokine receptor related genes, and chemokine related genes (Figures 5A-E).…”
Section: Discussionsupporting
confidence: 87%
“…It has been reported that TUBA1C, a multifunctional cytoskeleton protein, is a kind of α-tubulin subtype and that it is correlated with microtubules, participating in the progress of cellular mitosis and division ( Jordan and Wilson, 2004 ; Albahde et al, 2020 ). It has been revealed that high the expression of TUBA1C predicts a poor prognosis of hepatocellular carcinoma ( Wang et al, 2017 ), lung adenocarcinoma ( Bian et al, 2021 ), breast cancer ( Wang et al, 2019 ), and osteosarcomas ( Li et al, 2010 ). However, the role of TUBA1C in LGG and whether TUBA1C has immune-related biological functions in LGG have not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the most upregulated genes (>4-fold) in both Epha2-Q722 and Epha2-indel722 mutant lenses were those for tubulin alpha 1C (TUBA1C) and alkaline ceramidase-2 (ACER2). TUBA1C serves as a prognostic biomarker for a variety of cancers [64] and ACER2 is a Golgi enzyme involved in regulating B1 integrin maturation and cell adhesion [65]. In Epha2-Q722 and Epha2-null lenses, the gene for steroidogenic acute regulatory protein-related lipid transfer (START) domaincontaining protein 9 (STARD9) was strongly upregulated, whereas that for doublecortin domain-containing 2a (DCDC2a) was strongly upregulated in Epha2-indel722 and Epha2null lenses.…”
Section: Discussionmentioning
confidence: 99%